Glutathione produced by Rhizobium tropici is important to prevent early senescence in common bean nodules - Muglia, Cecilia Isabel (2008)
In this paper, we examine the importance of glutathione in symbiosis, using a glutathione biosynthetic gshB mutant derived from Rhizobium tropici CIAT899, a common bean (Phaseolus vulgaris) endosymbiont. Plants infected with the mutant strain presented a delayed nodulation phenotype and a reduction in the dry weight of aerial part of plants, suggesting diminished nitrogen-fixation activity. In addition, bacterial gshB expression was assayed in wild-type infected nodules, during the different steps of nodulation, and found to increase in mature and early senescent nodules. Conspicuously, nodules induced by gshB mutant bacteria presented an early senescent pattern, which was associated with increased levels of superoxide accumulation. These results provide a direct evidence of the role of bacterial glutathione in protecting nodules from reactive oxygen species, which may determine nodule senescence.